2011
DOI: 10.1002/dmrr.1185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin and oral anti‐diabetic agents on glucose metabolism, vascular dysfunction and skeletal muscle inflammation in type 2 diabetic subjects

Abstract: Background To test potential differences between the actions of anti-diabetic medications, we examined the effects of oral hypoglycemic agents versus insulin glargine-apidra therapy in T2DM. Methods T2DM subjects were randomized to either OHA (pioglitazone, metformin, glipizide, n=9) or IT (n=12) for 6 months. Carotid intimal media thickness (CIMT), vascular reactivity [FMD] (% change in brachial arterial diameter [BD] post-ischemia), and sublingual nitrate [SLN] were measured with ultrasonography. Euglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 56 publications
4
18
0
Order By: Relevance
“…Metformin has been reported to decrease hepatic glucose production, thereby activating AMPK, reducing fatty liver, and decreasing microvascular and macrovascular complications associated with type 2 diabetes (40). Several studies also have suggested additional benefits of metformin beyond hypoglycemic effects, including improvement of vascular function, regulation of vaspin levels and ovary function in polycystic ovary syndrome, adjuvant treatment for cancer, and disease prevention in prediabetic populations (4143). The anti-inflammatory effect of metformin also was demonstrated in neutrophils and acute lung injury mediated by mitochondrial complex I inhibition (44).…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been reported to decrease hepatic glucose production, thereby activating AMPK, reducing fatty liver, and decreasing microvascular and macrovascular complications associated with type 2 diabetes (40). Several studies also have suggested additional benefits of metformin beyond hypoglycemic effects, including improvement of vascular function, regulation of vaspin levels and ovary function in polycystic ovary syndrome, adjuvant treatment for cancer, and disease prevention in prediabetic populations (4143). The anti-inflammatory effect of metformin also was demonstrated in neutrophils and acute lung injury mediated by mitochondrial complex I inhibition (44).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies confirmed the presence of increased CIMT in people with type 2 diabetes or prediabetes (37). However, there are only a few small, and therefore not reliable, intervention trials with insulin on atherosclerosis progression (38,39). Clinical CV end point trials conducted prior to ORIGIN also fail to provide clear answers regarding the impact of exogenous insulin on CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Demonstrating improvement in vascular function with reductions in glucose is more difficult, because of confounding effects of most glucose-lowering therapies independent of benefits via glucose lowering. For example, glucose reductions with insulin therapy have been shown to improve endothelial function, but these benefits cannot be cleanly attributed to the glucose lowering effect alone [30,31]. Even therapies that modulate glucose concentrations independent of direct effects on beta cell function or insulin sensitivity in peripheral tissues can produce secondary improvements in these parameters, as will be discussed below.…”
Section: Therapies That Target the Endotheliummentioning
confidence: 99%